2022
DOI: 10.1186/s13256-022-03519-z
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment with mouthwashes followed by tongue photo biomodulation therapy in Covid-19: a case report

Abstract: Background Oral manifestations of coronavirus disease 2019 (COVID-19), including ulcers, herpetiform lesions, macules, and petechiae, among others, are becoming increasingly recognized, but there is little guidance on their treatment. Reported cases have described treatment with various mouthwashes containing antivirals, antifungals, antibiotics, anesthetics, or steroids. Our case report is unique in that we provide guidance on the judicious use of these medications, followed by photobiomodulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Oral lesions and skin lesions were also observed in the patient with COVID-19. The oral lesion was ulcer, 76 , 98 , 117 , 118 , 122 , 127 erosion and hemorrhagic crust, 98 blister, 98 depapilation, 72 desquamation 117 and erythema 76 , 117 —the skin lesion including the erythematous macula, urticaria, exanthema and perioral ulcer ( Table 10 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Oral lesions and skin lesions were also observed in the patient with COVID-19. The oral lesion was ulcer, 76 , 98 , 117 , 118 , 122 , 127 erosion and hemorrhagic crust, 98 blister, 98 depapilation, 72 desquamation 117 and erythema 76 , 117 —the skin lesion including the erythematous macula, urticaria, exanthema and perioral ulcer ( Table 10 ).…”
Section: Resultsmentioning
confidence: 99%
“… 38 , 41 , 42 , 47 , 55 , 56 , 60 , 61 , 80 , 94 , 96 , 98 , 125 , 127 , 132 Some studies also reported an occurrence of recurrent oral lesions, aphthous-like ulcers, 53 hemorrhagic ulcers 38 , 41 , 42 , 83 , 84 , 96 , 107 , 108 , 111 , 116 , 117 , 132 and macula (erythema). 42 , 55 , 56 , 76 , 80 , 81 , 91 While the findings often took place as an ulcer, other oral findings are also found in the form of plaques, 55 , 59 , 60 , 82 , 90 , 125 , 129 pseudomembrane, 38 , 39 , 42 , 46 , 55 , 59–62 , 77 , 81 , 91 , 92 , 94 , 111 , 127 , 129 depapilation, 38 , 39 , 41 , 72 , 74 , 113 , 127 or bleeding lesion. 37 , 94 , 95 , ...…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Photobiomodulation therapy (PBMT) or low-level laser therapy (LLLT) is a photon-based therapy that uses light to mediate a variety of metabolic, analgesic, anti-inflammatory, and immunomodulatory effects [138]- [140]. PBM devices typically deliver 10mW -500mW (0.01 -> 0.01 Watts) with a power density ranging from 0.005 W/cm 2 to 5 W/cm 2 .…”
Section: Clinical Studiesmentioning
confidence: 99%